Queering the 7-eyed model of clinical supervision. - Hawkins, Rima; Neves, Silva (Sexual & Relationship Therapy, 2025)
In this essay, we argue that the 7-eyed model of clinical supervision (as well as most models in psychotherapy) are in need of "queering." What we mean by "queering" is to make the model adaptable to the wider work with gender, sex, sexuality, erotic, and relationship diversities (GSERD) in clinical supervision. It is applicable to supervisors and/or supervisees and the clients who identify outside the societal heteronormative, mono-normative, and cisgenderist norms. Psychotherapy and psychology, and by extension, clinical supervision, have been criticised for being white, middle-class, heteronormative, and euro-centric. This article will provide a framework and guidance for clinical supervisors on how to adapt the 7-eyed model to diverse populations. LAY SUMMARY: The field of psychotherapy is generally embedded in white and heteronormative assumptions. These assumptions also apply to clinical supervision. This paper explains how we can adapt the 7-eyed model of clinical supervision to be more effective for clients and supervisees who are outside of the societal norms and marginalised, to foster an anti-oppressive practice.